Prevalence of microalbuminuria among adults with Type 2 Diabetes mellitus at OOUTH, Sagamu - Amballi Adebayo Adetola; Odusan Olatunde; Ogundahunsi Omobola Abioye; Jaiyesimi Alfred Ademola; Oritogun Kolawole Sunday; Olooto Eniola Wasiu (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2018)
Background: Diabetes mellitus is a serious global epidemic. The menace of this chronic disease is attributable to its chronic complications which threaten both the world economy and life expectancy, especially in Sub- Saharan Africa. Nephropathy is a complication of Diabetes mellitus and a leading cause of End Stage Renal Disease. Objectives: To determine the prevalence of microalbuminuria as well as the effects of co-morbidities on the pattern of microalbuminuria among adults with Type 2 Diabetes mellitus. Methods: A total of 325 adults with Diabetes mellitus and 100 controls without Diabetes mellitus were studied. The subjects with diabetes were classified into four groups ([i] diabetes only, [ii] diabetes with hypertension, [iii] diabetes with obesity and [iv] diabetes with hypertension and obesity). Urinary protein, microalbuminuria, fasting plasma glucose and Glycated Haemoglobin (HbA1c) were measured using standard methods. Results: The overall prevalence of microalbuminuria was 35.1% in the diabetic population compared to 8.0% in the control group. The prevalence of microalbuminuria in the various diabetic subgroups were as follows: 30.3% (diabetes only), 43.1% (diabetes with hypertension), 37.0% (diabetes with obesity) and 44.6% (diabetes with hypertension and obesity). The fasting plasma glucose and HbA1c were statistically significantly higher in the diabetic population than the control group. This indicated that there is a poor glycaemic control in the diabetic population and hence a possible cause of diabetic nephropathy. Conclusion: The risk of diabetic nephropathy was significant in the study population. The presence of one or more co-morbidities and poor glycaemic control increased the occurrence of diabetic nephropathy.